Basel III LCR Requirement and Banks' Deposit Funding: Empirical Evidence from Emerging Markets - Tafirei Mashamba; Rabson Magweva (Journal of Central Banking Theory and Practice, 2019)
In December 2010, the Basel Committee on Baking Supervision introduced the liquidity coverage ratio (LCR) standard for banking institutions in response to disturbances that rocked banks during the 2007/08 global financial crisis. The rule is aimed at enhancing banks' resilience to short term liquidity shocks as it requires banks to hold ample stock of high grade securities. This study attempts to evaluate the impact of the LCR specification on the funding structures of banks in emerging markets by answering the question "Did Basel III LCR requirement induced banks in emerging market economies to increase deposit funding more than they would otherwise do?" The study found that the LCR charge has been effective in persuading banks in emerging markets to garner more stable retail deposits. This response may engender banking sector stability if competition for retail deposits is properly regulated.
Keywords: G11; G18; G19; G21; G28; 330; Basel III; LCR; commercial banks; emerging market economies.